2021
DOI: 10.1016/j.cej.2020.127419
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and mass transfer modelling for extractive desulfurization of diesel with ionic liquid in microreactors

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 55 publications
1
23
0
1
Order By: Relevance
“…The submillimeter microscale continuous flow process is particularly of significance to fast exothermic and complex reactions, such as polymerization and radical reactions involving unstable intermediates or toxic reagents (Kim et al, 2004;Zaborenko et al, 2010). In our series of studies on microreactor technology, we have successfully developed a range of droplet-based microreactors, demonstrating the capability and suitability for effective multiphase reactions by regulating hydrodynamics, interface characteristics and overall mass transfer (Zhang et al, 2018;Ma et al, 2019;Zhou et al, 2020;Hao et al, 2020;Sun et al, 2021;Jin et al, 2021). Furthermore, microreactors have been shown as a promising platform for the characterization of chemical reaction kinetics, mainly due to the high degree of controllability over the multiphase microenvironment (Zaborenko et al, 2010;McMullen et al, 2011;Wang et al, 2011;Su et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The submillimeter microscale continuous flow process is particularly of significance to fast exothermic and complex reactions, such as polymerization and radical reactions involving unstable intermediates or toxic reagents (Kim et al, 2004;Zaborenko et al, 2010). In our series of studies on microreactor technology, we have successfully developed a range of droplet-based microreactors, demonstrating the capability and suitability for effective multiphase reactions by regulating hydrodynamics, interface characteristics and overall mass transfer (Zhang et al, 2018;Ma et al, 2019;Zhou et al, 2020;Hao et al, 2020;Sun et al, 2021;Jin et al, 2021). Furthermore, microreactors have been shown as a promising platform for the characterization of chemical reaction kinetics, mainly due to the high degree of controllability over the multiphase microenvironment (Zaborenko et al, 2010;McMullen et al, 2011;Wang et al, 2011;Su et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The continuous EDS experiments were carried out on a similar setup to Figure , where all the microchannels were immersed into a heating bath rather than embedded in a visualization cell. For details, refer to our previous article . The experiments were conducted at a Q d / Q c ratio of 0.1–0.5, a constant total volumetric flow rate ( Q t ) of 550 μL/min, and an extraction temperature of 30–60 °C.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the mass transfer mechanism and kinetics of IL-EDS are worthy of further study to provide theoretical guidance for process design and extractor development. The fluid flow in a microreactor is usually highly ordered and has a narrow residence time distribution and good periodic repeatability, all of which are convenient for an accurate theoretical description of mass transfer. , Based on the well-defined slug flow, Van Baten et al and Matsuoka et al verified that the mass transfer between two phases proceeds through the lateral side of the (bubble) droplet as well as the end interface. In the extraction of rhodamine 6G from water to [BMIM]­[PF 6 ], it is found that the mass transfer coefficient at the droplet formation stage was 3–4 times larger than that at the moving stage, caused by stronger disturbance inside the droplet at the formation stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we all know, the traditional desulfurization technology (hydrodesulfurization (HDS)) requires hydrogen under severe operating conditions (high temperatures and pressures) as well as it is unable to remove aromatic sulfur compounds such as DBT. 5 , 6 Considering the above-mentioned reasons, alternative technologies are under development, and they are adsorption, 7 , 8 bio-desulfurization (BD), 9 extractive desulfurization (ExD), 10 and oxidative desulfurization (ODS). 11 Among them, oxidative desulfurization could be a viable process for the removal of sulfur species from fuel oil owing to its high efficiency, economic aspect, eco-friendliness, low energy cost, handiness, and resistance to harsh operating conditions.…”
Section: Introductionmentioning
confidence: 99%